Light Wave Digital Learning Material with Augmented Reality and CTL Model to Improve Students' 4C Skill - Novit, Insyirah Erlenida; Virijai, Febrian; Asrizal (Journal of Education Reseach and Evaluation, 2023)
The learning in 21st century should implement students' 21st century skills, known as 4C skills. These skills are needed by students to face global competition in the future. The preliminary research results show that skills of 4C by students are still lack. The way for fix the problem is that students need learning media that is more interactive and attracts interest in learning. Digital learning materials with Augmented Reality integrated with CTL models are a solution to the problem. The research purpose was to analyze the needs analysis, validity, and practicality of using digital learning materials with an AR integrated CTL model. This research method uses research and development using the Hannafin & Peck development model. The research instruments include a needs analysis instrument, a validation questionnaire sheet, and a practicality questionnaire sheet. The techniques for data analysis used are descriptive, qualitative, and quantitative statistics. Based on the data that has been analysed, there are three research results. First, the needs analysis research results stated that the low 4C skills of students. Second, the product validation results obtained an average value of 0.8 in the category was valid. Third, the product practicality results obtained an average value of 86 in the very practical category. The research results implication are that digital teaching materials with AR and CTL can be used as alternative learning resources to achieve learning goals, then teachers can construct students' 4C skills by using AR-CTL Physics digital teaching material.